2019
DOI: 10.3390/ijerph17010121
|View full text |Cite
|
Sign up to set email alerts
|

Living a Healthy Life in Australia: Exploring Influences on Health for Refugees from Myanmar

Abstract: Background: Humanitarian migrants from Myanmar represent a significant refugee group in Australia; however, knowledge of their health needs and priorities is limited. This study aims to explore the meaning and influencers of health from the perspectives of refugees from Myanmar. Method: Using a community-based participatory research (CBPR) design, a partnership was formed between the researchers, Myanmar community leaders and other service providers to inform study design. A total of 27 participants were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
6
0
3
Order By: Relevance
“…The Bendigo Community Health Services recognized that information about health responses to the pandemic shared via mainstream mechanisms such as television, radio, and leaflets written in English were unlikely to reach and be effective with Karen community members. These observations and in-practice learnings of BCHS are further supported by research that indicated the Karen community has less access to mainstream news and low levels of health literacy (9,10). Furthermore, they report lower uptake and use of digital technology than the wider Australian community, and as a former-refugee community, they are located on the "digital fringe" (11).…”
Section: Community-based Program Designmentioning
confidence: 71%
“…The Bendigo Community Health Services recognized that information about health responses to the pandemic shared via mainstream mechanisms such as television, radio, and leaflets written in English were unlikely to reach and be effective with Karen community members. These observations and in-practice learnings of BCHS are further supported by research that indicated the Karen community has less access to mainstream news and low levels of health literacy (9,10). Furthermore, they report lower uptake and use of digital technology than the wider Australian community, and as a former-refugee community, they are located on the "digital fringe" (11).…”
Section: Community-based Program Designmentioning
confidence: 71%
“…Yet, elderly refugees are still vulnerable and need awareness, capacity building and specific measures in the humanitarian response. Research shows that many elderly individuals face the conditions of frailty, lack of mobility and chronic health problems, that can become acute and life threatening as a result of stressful experiences of displacement (Birditt, et al, 2018;Wong, et al, 2020;Koochek, et al,2007). Moreover, UNHCR reports that "older refugees make up about8.5 per cent of the overall population of concern to UNHCR, and by 2050 more of the world will be over 60 than under 12."…”
Section: Lack Of Data On Elderly Issuesmentioning
confidence: 99%
“…Pekerjaan merupakan pengaruh utama terhadap kesihatan orang pelarian (Wong et al, 2019;Wood et al, 2019;Yijala & Luoma, 2019). Sebagai contoh, kajian oleh Wood et al (2019) mendapati orang pelarian Afrika di Australia berasa lebih sihat secara keseluruhan apabila bekerja, melalui aktiviti fizikal pekerjaan itu sendiri, serta dengan wujudnya rutin dan tujuan harian.…”
Section: Pekerjaanunclassified
“…Sebagai contoh, kajian oleh Wood et al (2019) mendapati orang pelarian Afrika di Australia berasa lebih sihat secara keseluruhan apabila bekerja, melalui aktiviti fizikal pekerjaan itu sendiri, serta dengan wujudnya rutin dan tujuan harian. Sama seperti kajian oleh Wong et al (2019), mereka mendapati pekerjaan secara tidak langsung memberi manfaat kepada kesihatan fizikal orang pelarian Myanmar di Australia melalui perjalanan pergi dan balik ke tempat kerja, serta semasa melakukan pekerjaan itu sendiri. Di samping itu, pekerjaan mendatangkan kesan positif bukan sahaja terhadap kesihatan fizikal, malah kesihatan psikologi dan kepuasan hidup orang pelarian (Yijala & Luoma, 2019).…”
Section: Pekerjaanunclassified
See 1 more Smart Citation